Accounting Standards and International Portfolio Holdings - Yu, Gwen; Wahid, Aida Sijamic (The Accounting Review, 2014)
ABSTRACT Do differences in countries' accounting standards affect global investment decisions? We explore this question by examining how accounting distance, the difference in the accounting standards used in the investor's and the investee's countries, affects the asset allocation decisions of global mutual funds. We find that investors tend to underweight investees with greater accounting distance. Using the mandatory adoption of International Financial Reporting Standards (IFRS) as an event that changed the accounting standards of various country-pairs, we examine how two sources of changes in accounting distance—(1) changes due to IFRS adoption of the investee, and (2) changes due to IFRS adoption in the investor's country—affect global portfolio allocation decisions. We find that the tendency to underinvest in investees with greater accounting distance significantly weakens when accounting distance is reduced, either from an investee's IFRS adoption or from IFRS adoption in the investor's country. The latter finding holds despite the fact that IFRS adoption in the investor's country had no impact on the accounting standards under which the investee firms present their financial information; the only change is in the investor's familiarity with these standards. This suggests that differences in accounting standards affect investor demand by imposing greater information-processing costs on those less familiar with the reporting standards.